2019
DOI: 10.12968/ijtr.2018.0054
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of Otago Exercise Programme and Prevention of Falls for Adults with Intellectual Disability: a multiple case study design

Abstract: Background/Aims Many people with intellectual disability fall frequently. Understanding fall prevention intervention characteristics will assist efficacy trials to target appropriate people. An exploration of two exercise-based fall prevention interventions is reported, focusing on viability and acceptability. Methods A multiple case study of adults with intellectual disability completing either the group Otago Exercise Programme or the Prevention of Falls for Adults with Intellectual Disability intervention w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Falls prevention interventions for people with intellectual disabilities have included: Obstacle course training (Van Hanegem et al, 2014); Aquatic exercise (Nissim et al, 2019); Modified Otago Exercise Programme (OEP) (Hale et al, 2019; Renfro et al, 2016); Multi‐component balance‐specific exercise programme (Kovacic et al, 2020); Vestibular rehabilitation programme (Cortes‐Amador et al, 2019); Tailored multifactorial risk assessment and intervention strategy (Smulders, Enkelaar, Schoon, et al, 2013b); Trial of lycra splinting clothing to improve balance (Finlayson et al, 2018); Prevention Of Falls for Adults with Intellectual Disabilities (PROFAID) intervention (Hale et al, 2016, 2019); Falls prevention treatment pathway (Crockett et al, 2015); Usual care by Therapists (Pal et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Falls prevention interventions for people with intellectual disabilities have included: Obstacle course training (Van Hanegem et al, 2014); Aquatic exercise (Nissim et al, 2019); Modified Otago Exercise Programme (OEP) (Hale et al, 2019; Renfro et al, 2016); Multi‐component balance‐specific exercise programme (Kovacic et al, 2020); Vestibular rehabilitation programme (Cortes‐Amador et al, 2019); Tailored multifactorial risk assessment and intervention strategy (Smulders, Enkelaar, Schoon, et al, 2013b); Trial of lycra splinting clothing to improve balance (Finlayson et al, 2018); Prevention Of Falls for Adults with Intellectual Disabilities (PROFAID) intervention (Hale et al, 2016, 2019); Falls prevention treatment pathway (Crockett et al, 2015); Usual care by Therapists (Pal et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…The changes were generally found to be greater for the younger group of participants <50 years, suggesting that reduction of fall risk can occur at an earlier age among people with intellectual disabilities (Renfro et al, 2016). These findings suggest that whilst the PROFAID and OEP interventions may be feasible in the prevention of falls among people with intellectual disabilities, the logistics of how such interventions can be delivered appropriately, acceptably, clinically and cost‐effectively and sustainably needs further investigation (Hale et al, 2016, 2019). Pal et al (2013) investigated Therapists' views on how to reduce the risk of falls in people with intellectual disabilities and found that a combination of participation in physical exercise, prescription of assistive mobility devices, environmental modifications, and education on safe mobility were thought to be the most useful interventions.…”
Section: Resultsmentioning
confidence: 99%
“…The movement of OEP is not complex. Hale L and other ( 56 ) scholars took adults with slight intellectual impairment as the research object and found that it is not too difficult for patients to understand the content of OEP and can complete their training movements. Therefore, it is suggested that older adult with cognitive decline do not have too much psychological pressure and burden when completing.…”
Section: Resultsmentioning
confidence: 99%
“…Participant's inability to comprehend the need for, or the importance, of engaging in falls prevention strategies has also been described as a barrier to reducing falls risk for adults with intellectual disability (Pal et al, ). Previous research has identified increasing the level of awareness about falls encourages the engagement in falls prevention interventions (Hale, Vollenhoven, Caiman, Dryselius, & Buttery, ).…”
Section: Discussionmentioning
confidence: 99%